Continuous-wave green laser irradiation to form PbS quantum dots in glass - Jong Heo; Byoungjin So; Zhiyong Zhao; Tihitnaw Fentahun Degu (Journal of Non-Crystalline Solids: X, 2022)
PbS quantum dots (QDs) are appropriate for use in tunable optoelectronic devices such as optical amplifiers because of their large Bohr exciton radii (18 nm). Laser-assisted local heating around Ag NPs can provide an effective method for site selective precipitation and for controlling the size of QDs. Continuous wave (CW) laser irradiation has been applied on a Ag+-ion exchanged glass which lead to the precipitation of QDs PbS QDs of 5-nm diameter were precipitated after 3 min of CW laser illumination at 1.5 W. The PbS QDs showed a PL peak at λ ∼ 1490 nm, which shifted toward longer wavelength side as duration of Ag+ ion exchange and of laser illumination increased. This method was further applied to prepare a rod containing three sections with different diameters of PbS QDs to propose the possibility of developing broadband amplifiers to cover the 1.3–1.7 μm communication window using one glass fiber. Co2+ also absorbs 532 nm laser light and converts it to thermal energy that results in the precipitation of PbS QDs in the glass matrix. The emission peak of the QDs covers 1020 nm < λ < 1245 nm as laser power was increased from 6 to 7 W/cm2. Temperature in the glass increased to ∼518 °C when it was illuminated at the intensity of 6 W/cm2.